Progress and modernity: the problem with autonomy - Wagner, Peter (Sociología Histórica, 2017)
The idea of modernity is inextricably tied up with the one of progress. One main reason for this connection is that the late eighteenth century, often considered to be the onset of modernity, was in Europe also seen as the dawn of a new society evolving according to a different logic than any preceding one, namely with an open horizon of future possibilities. This article explores the meaning of this opening by first looking at the elaboration of what is called here a “strong concept of progress”, based on the connection between autonomy and reason, and by subsequently confronting this concept with the historical experiences with progress. This confrontation helps to understand the transformations in the expectations of progress from the middle of the nineteenth to the middle of the twentieth century. As a result a more nuanced view of the relation between progress and modernity will be proposed that can be fruitful for assessing our current expectations of progress in the context of contemporary modernity.